PRAKSIS STRATEGI PEMBELAJARAN KEJURUAN BIDANG AGRIBISNIS ABAD 21 - Hestina Windiyati (Universitas Sarjanawiyata Tamansiswa, 2017)
The challenges facing vocational education in the 21st century are increasingly complex. The demands of work in the global era require a creative, innovative, initiative, leadership, independent, able to work in a team, literacy skills, effective communication skills, problem-solving skills, and entrepreneurship skills. This study aims to describe the praxis of vocational learning strategies of field agribusiness in 21st century. Some praxis of Â learning strategies that are relevant to the field of agribusiness, namely 1) entrepreneurial approach, 2) industrial work practices, 3) teaching factory, 4) project work, 5) Problem-Based Learning, 6) Discovery Learning 7) Inquiry Learning, 8) Contextual Learning, 9) Jigsaw Learning.